"In the midst of the Jordan": the Jordan Valley during the middle bronze age (circa 200 - 1500 BCE); archaeological and historical correlates - Maʾir, Aharon (Denkschriften der Gesamtakademie, 2010)
Literaturverz. S. [253] - 296